Antagonism Mechanism of Epiphytic Yeast against Anthracnose Pathogen (Colletotrichum acutatum) on Chilli - Sri Hartati; Suryo Wiyono; Sri Hendrastuti Hidayat; Meity Suradji Sinaga (Jurnal Perlindungan Tanaman Indonesia, 2019)
Epiphytic yeasts have the potency as antagonistic agents against various pathogens of post-harvest products. Anthracnose is a major disease of chilli that causes high economic loss. This research was objected to study the antagonism mechanism of epiphytic yeast isolates that have the antagonistic potency against anthracnose pathogen on chilli (Colletotrichum acutatum). Twenty-two isolates of epiphytic yeasts, isolated from chilli leaves and fruit, were tested. The characterization of the antagonism was carried out by antibiosis, anti-fungus volatile production, and chitinolytic activity tests. The results showed that all tested isolates did not have antibiosis mechanism against C. acutatum. All isolates produced volatile compounds which inhibited the colony growth of C. acutatum. Four isolates showed high relative inhibition rate, i.e. isolates B32DEP (35.68%), B30DEP (37.52%), B23DEP (38.52%), and B29DEP (45.42%). Fourteen isolates showed chitinolytic activities. Three of them had high chitinolytic activities, i.e. B12DEP, B2DEP, and G237DEP.